Full Black: Scot Harvath #10 - Thor, Brad (New York : Atria Books, 2011)
As terrorists conspire to unleash a series of deadly attacks across America and a foreign wet work team targets a famous Hollywood filmmaker, counterterrorism operative Scot Harvath races against time to save the United States from complete collapse.
Keywords: Harvath, Scot (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Harvath, Scot (Fictional character) -- Fiction; Intelligence service -- United States -- Fiction; Suspense fiction; Mystery fiction